2019
DOI: 10.1017/pen.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

Increases in theta CSD power and coherence during a calibrated stop-signal task: implications for goal-conflict processing and the Behavioural Inhibition System

Abstract: Psychologists have identified multiple different forms of conflict, such as information processing conflict and goal conflict. As such, there is a need to examine the similarities and differences in neurology between each form of conflict. To address this, we conducted a comprehensive electroencephalogram (EEG) analysis of Shadli, Glue, McIntosh, and McNaughton’s calibrated stop-signal task (SST) goal-conflict task. Specifically, we examined changes in scalp-wide current source density (CSD) power and coherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…Revealing similar topographies as the NOGO trials, STOP trials also showed delta and theta band power to be significantly decreased in frontal sensors in the HI group compared to the LI group. This is consistent with a recent EEG study showing increased mid-frontocentral theta and increased delta in posterior sensors during STOP trials, in healthy participants (Lockhart et al, 2019). Present findings suggest reduced delta and theta band power in frontal regions might reflect reduced inhibitory processing in high impulsivity individuals during NOGO and STOP trials.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Revealing similar topographies as the NOGO trials, STOP trials also showed delta and theta band power to be significantly decreased in frontal sensors in the HI group compared to the LI group. This is consistent with a recent EEG study showing increased mid-frontocentral theta and increased delta in posterior sensors during STOP trials, in healthy participants (Lockhart et al, 2019). Present findings suggest reduced delta and theta band power in frontal regions might reflect reduced inhibitory processing in high impulsivity individuals during NOGO and STOP trials.…”
Section: Discussionsupporting
confidence: 93%
“…Increased theta band power has been proposed to be essential for response inhibition as an integrative mechanism of early stimulus detection and response selection processes (Cavanagh and Frank, 2014; Mückschel et al, 2017). Although the literature on spectral analysis of the SST is very limited, a recent EEG study using scalp-wide current source density transformation (CSD), found increased mid-frontocentral theta and frontal delta during STOP conditions (Lockhart et al, 2019). It could be argued that in individuals scoring high on impulsivity and showing worse task performance, delta and theta band power might be reduced in NOGO and STOP conditions, reflecting an impairment in motor inhibition, compared to those scoring low and performing better.…”
Section: Introductionmentioning
confidence: 99%
“…It also follows that, where they are ligands of the relevant receptors, drugs can be used to develop biomarkers for state (and so by derivation trait) measures of these systems. In the case of trait GIS (the basis for one possible "trait anxiety" factor), we already have at least one such biomarker (McNaughton, 2018;Shadli et al, 2019;Shadli et al, 2015) with others awaiting drug validation (Lockhart, Moore, Bard & Stafford, 2019;Moore, Gale, Morris & Forrester, 2008;Moore, Mills, Marsham & Corr, 2012).…”
Section: Discussionmentioning
confidence: 99%